VD_FINDINFO Jug / 2012 / 314 vom 5. April 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, MISE EN LIBERTÉ PROVISOIRE, SOUPÇON, PROPORTIONNALITÉ | 221 CPP (CH), 222 CPP (CH), 228 CPP (CH), 393 al. 1 let. b CPP (CH)